Stationary and Oscillatory Flow of the Reiner-Rivlin Fluid Between Two External Rollers - Miksa, M. (Engineering Transactions, 1996)
In a certain class of thin-layer viscoelastic flows, the extensional parts of deformation are much greater than the shearing ones. For such flows we may apply the model of the Reiner-Rivlin fluid [1]. This concept is applied to the stationary and oscillatory flow between two rotating external cylinders. The approximate solutions are presented and possible effects of the extensional viscosity function on the loads and friction forces are discussed.